(untitled) (Revista Direito em Debate, 2022)
With the Brazilian reality of the overcrowding of lawsuits and the sluggishness of the Judiciary, there is a dissatisfaction of citizens in meeting their concerns. It is in this context that technology emerges as a tool to solve these problems and, in turn, Legal startups propose innovative solutions that can speed up conflict resolution. Thus, this study aimed to analyze the modernization of Law in the light of the impact that Legal startups promoted in the scope of the application of this science. As for the methodology, the research is classified as qualitative, through content analysis. Among the results, one can note the rise of startups in the market, however there are still challenges to be overcome, such as the validation of these companies, the creation of a safer virtual environment, the high cost of technology and the concern to maintain the human aspect of Law, effectively ensuring justice. Nevertheless, it is concluded that Legal startups represent a means of simplifying the legal exercise and promoting not only access to the Judiciary, but the resolution of conflicts.